Penanganan Awal pada Berbagai Jenis Luka Akut - Nuridah Nuridah; Yuniarti Ekasaputri Burhanuddin; Yodang Yodang (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Injuries that often cause injuries often happen to anyone and anywhere, and it is not uncommon for wounds to be difficult to heal and even become scars that cannot be removed due to ineffective wound care. The role of health educators is by providing education in community service activities through the practice of